O tradycjach, zadaniach i wyzwaniach czeskiej polonistyki literackiej - Kardyni-Pelikanová, Krystyna (Slavia Occidentalis, 2011)
The article presents a brief survey of the history of the Polish literary studies in the Czech Republic and the subsequent paradigms of the scholarly research which this branch of knowledge adopted. The author also ponders over the way of arranging and presenting the literary material on lectures and Polish language seminars as well as over the ways of educating Polish philologists outside Poland, in the time of ever firmer cross-cultural relationships, involvement in relations, the dialogue of cultures.